Brief Report: Impact of the COVID-19 Pandemic on Virological Suppression in People Living With HIV Attending a Large Italian HIV Clinic. (1st November 2021) - Giacomelli, Andrea; Bonazzetti, Cecilia; Conti, Federico; Pezzati, Laura; Oreni, Letizia; Micheli, Valeria; Mancon, Alessandro; Vimercati, Stefania; Albrecht, Maria; Passerini, Matteo; Cossu, Maria Vittoria; Capetti, Amedeo Ferdinando; et al.
Abstract : Background: We assessed the impact of the coronavirus disease 2019 (COVID-19) pandemic on HIV suppression rates in people living with HIV (PLWH) attending a large Italian HIV clinic. Setting: The HIV outpatient clinic of the Infectious Diseases Department of Luigi Sacco Hospital, Milan, Italy, which serves more than 5000 PLWH per year. Methods: A before and after quasi -experimental study design was used to make a retrospective assessment of the monthly trend of HIV-RNA determinations of ≥50 among the PLWH attending our clinic, with "before" being the period from January 1, 2016 to February 20, 2020, and "after" being the period from February 21, 2020 to December 31, 2020 (the COVID-19 period). Interrupted time series analysis was used to evaluate any changes in the trend. Results: During the study period, 70, 349 HIV-RNA viral load determinations were made, and the percentage of HIV-RNA viral load determinations of <50 copies/mL increased from 88.4% in 2016 to 93.2% in 2020 ( P < 0.0001). There was a significant monthly trend toward a decrease in the number of HIV-RNA determinations of ≥50 copies/mL before the pandemic (β −0.084; standard error 0.015; P < 0.001), and this did not significantly change after it started (β −0.039, standard error 0.161; P = 0.811). Conclusions: A high prevalence of viral suppression was maintained among the PLWH referring to our clinic, despite the structural barriers raised by the COVID-19 pandemic. The use of simplified methods of delivering care (such as teleconsultations and multiple antiretroviral treatment prescriptions) may have contributed to preserving this continuum.